Quantification of perfusion in murine myocardium: A retrospectively triggered T1‐based ASL method using model‐based reconstruction. Issue 6 (1st December 2014) - Gutjahr, Fabian T.; Kampf, Thomas; Winter, Patrick; Meyer, Cord B.; Williams, Tatjana; Jakob, Peter M.; Bauer, Wolfgang R.; Ziener, Christian H.; Helluy, Xavier
Abstract : Purpose: A method for the quantification of perfusion in murine myocardium is demonstrated. The method allows for the reconstruction of perfusion maps on arbitrary time points in the heart cycle while addressing problems that arise due to the irregular heart beat of mice. Methods: A flow‐sensitive alternating inversion recovery arterial spin labeling method using an untriggered FLASH‐read out with random sampling is used. Look‐Locker conditions are strictly maintained. No dummy pulses or mechanism to reduce deviation from Look‐Locker conditions are needed. Electrocardiogram and respiratory data are recorded for retrospective gating and triggering. A model‐based technique is used to reconstruct missing k‐space data to cope with the undersampling inherent in retrospectively gated methods. Acquisition and reconstruction were validated numerically and in phantom measurements before in vivo experimentation. Results: Quantitative perfusion maps were acquired within a single slice measurement time of 11 min. Perfusion values are in good accordance to literature values. Myocardial infarction could be clearly visualized and results were confirmed with histological results. Conclusion: The proposed method is capable of producing quantitative perfusion maps on arbitrary positions in the heart cycle within a short measurement time. The method is robust against irregular breathing patterns and heart rate changes and can be implemented on all scanners. Magn Reson Med 74:1705–1715, 2015. © 2014 Wiley Periodicals, Inc.